2022
DOI: 10.1002/cjoc.202200123
|View full text |Cite
|
Sign up to set email alerts
|

Concise Total Synthesis of Dysoxylactam A and a Simplified Analog

Abstract: Comprehensive Summary A total synthesis of 17‐membered macrocyclolipopeptide dysoxylactam A, a potent agent reversing P‐glycoprotein (P‐gp)‐mediated multidrug resistance (MDR) in cancer cells, was developed from the starting material (S)‐2‐methylbutanal in a linear sequence of 12 steps with 23.2% overall yield. The key steps include proline‐catalyzed asymmetric aldol reaction, Evans aldol reaction and Krische allylation to construct the multiple stereocenters containing fragment, and ring‐closing metathesis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Chemical transformations, especially oxidation and reduction reactions, are very practical in the structural elucidation of complex natural products. [10][11][12][13][14] As shown in Scheme S1, † compound 1 could be biogenetically generated by oxidative cleavage of the Δ 3 double bond of 2. In order to determine the relative and absolute configurations of 1, we attempted to develop selective, high-yielding and operationally simple oxidation methods for the conversion of 2 to 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical transformations, especially oxidation and reduction reactions, are very practical in the structural elucidation of complex natural products. [10][11][12][13][14] As shown in Scheme S1, † compound 1 could be biogenetically generated by oxidative cleavage of the Δ 3 double bond of 2. In order to determine the relative and absolute configurations of 1, we attempted to develop selective, high-yielding and operationally simple oxidation methods for the conversion of 2 to 1.…”
Section: Resultsmentioning
confidence: 99%
“…of chemical transformations in the structural elucidation of complex natural products. [10][11][12][13][14] Biological assays revealed that compounds 1-7 showed moderate immunosuppressive effects against concanavalin A (ConA)-induced proliferation of T lymphocytes and lipopolysaccharide (LPS)-induced proliferation of B lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40−43 In this regard, macrocycles offered a promising opportunity for developing novel P-gp inhibitors with both higher potency and better safety profiles. Interestingly, in most cases, the macrocyclic P-gp inhibitors were discovered from natural products (Figure 1A), 44−48 such as jatrophane diterpenoids, 45 dysoxylactam A, 44,49 and cyclolipopeptides. 46 Despite the attractive characteristics offered by them, the difficulty of resupply and limitation of modification sites would hamper the investigations of their structure−activity relationship (SAR) and in vivo antitumor efficacy.…”
Section: ■ Introductionmentioning
confidence: 99%
“…During recent years, macrocycles as a unique scaffold have received increasing attention in medicinal chemistry due to their 3D conformation and proper flexibility and rigidity, which can favorably alter the biological and physiochemical properties and selectivity in comparison to the acyclic analogue. In this regard, macrocycles offered a promising opportunity for developing novel P-gp inhibitors with both higher potency and better safety profiles. Interestingly, in most cases, the macrocyclic P-gp inhibitors were discovered from natural products (Figure A), such as jatrophane diterpenoids, dysoxylactam A, , and cyclolipopeptides . Despite the attractive characteristics offered by them, the difficulty of resupply and limitation of modification sites would hamper the investigations of their structure–activity relationship (SAR) and in vivo antitumor efficacy.…”
Section: Introductionmentioning
confidence: 99%